ANALISIS PREDIKSI POTENSI RISIKO FRAUDULENT FINANCIAL STATEMENT MELALUI PERSONAL FINANCIAL NEED DAN AUDITOR SWITCHING - Werastuti, Desak Nyoman Sri (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 1 (2015), 2015)
This study intends to analyze and detect the presence or absence of the potential risk of fraudulent financial statements using pressure risk factors that proxied by personal financial need and the rationalization that is proxied by the auditor switching. This research is important because the number of fraud cases handled by Bapepam be evidence that there is a failure to detect fraud audit financial statements. The scarcity of research in Indonesia which predict fraud in the financial statements using the personal analysis of financial need and auditor switching to undertake testing of these variables. The sample of this research is manufacturing companies listed in Indonesia Stock Exchange in 2011-2013 with amount is 116 companies. Hypothesis testing is performed with logistic regression. The results of this study are personal financial need as measured by ownership of people in a positive effect on fraudulent financial statements. This means that the higher the percentage of ownership by people in the practice of fraud in manipulating financial statements increased. Auditor switching is not influential in predicting fraudulent financial statements. That is changing whether or not the firm conducting the audit, it is possible to detect fraud in the financial statements depending on skepticism auditors conduct audits.
Keywords: fraudulent financial statement, personal financial need, auditor switching